Urban traffic's energy saving and emission reduction device - WAN CHANG (2018)
The utility model discloses an urban traffic's energy saving and emission reduction device, its structure includes air inlet, inlet port, active carbon filter screen, muffler, connecting pipe, gas outlet, and the left end of air inlet is fixed on the surface to be equipped with the inlet port, and the inlet port meshes with the active carbon filter screen mutually, and the left side of connectingpipe is connected with the air inlet, and the gas outlet is connected in the right side of connecting pipe, and the inside of connecting pipe is located to the muffler, the utility model discloses beequipped with the active carbon filter screen, realized that this urban traffic's energy saving and emission reduction device possess the high adsorption performance that can adopt the active carbon and can come tail gas purification when using to the effectual tail gas that has reduced is to atmospheric pollution when discharging, and is energy -concerving and environment -protective. 本实用新型公开了种城市交通的节能减排装置，其结构包括进气口、进气孔、活性炭